PRE-SERVICE ENGLISH TEACHERS’ PERCEPTIONS OF GLOBAL ENGLISHES-INFORMED LANGUAGE TEACHING - Wahyudi, M. Dicky Indra; Suharyadi, Suharyadi; Sujiatmoko, Ahmad Heki (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2026)
This study explores pre-service English teachers’ perceptions of Global Englishes-informed language teaching within a teacher education context. Drawing on a quantitative survey design, the study examines three key dimensions: attitudes, confidence, and intentions toward the pedagogical application of Global Englishes. The participants were students enrolled in a master’s degree program in English education. Data were collected using a structured questionnaire and analyzed using descriptive statistics. The findings indicate that participants generally demonstrate positive attitudes toward Global Englishes. However, their confidence in applying its principles was comparatively lower than their attitudes and intentions. The results also suggest that prior exposure to different forms of English, such as through media and interaction, may be associated with more flexible perceptions of English use. This study provides exploratory insights into how pre-service teachers conceptualize Global Englishes and its relevance for teaching. The findings highlight the importance of addressing not only attitudes but also confidence and pedagogical readiness in teacher education programs. These results may inform future research and contribute to ongoing discussions on Global Englishes-informed pedagogy in English language teaching.